ANALISA CYCLE TIME PADA INDUSTRI PERSENJATAAN NASIONAL UNTUK MEMPERCEPAT HASIL PRODUKSI SENJATA DAN MEMPERKUAT PERTAHANAN NASIONAL - Mildiawan, Handra; Pardamean , Victor; Budiarto, Manahan (AGUSPATI Research Institute, 2022)
Technology at this time continues to develop. With the advancement of technology, developments in the military world will also develop rapidly. Projectiles are an important component in bullets and weapons. This research will discuss and analyze related to the production line and the process of making projectiles. The balance and speed of the production line in making projectiles will be prioritized here. This projectile production line already has a fairly balanced amount of cycle time. The average production process in the projectile making industry is 10 seconds with the first process, namely Annealing, taking 11 seconds, the second process, namely Cold Rolling, taking 9 seconds to make one projectile, the third process, namely lathe, requiring a fairly short time because the projectile itself does not really require a long lathe time, namely 9 seconds, then the 4th process, namely Machining, this process is actually similar to the lathe process but requires considerable accuracy and smoother results. This process takes 11 seconds to make projectiles. The last is the process of finishing this process is the last gate for all processes that have been run, this process takes 10 seconds. With this balanced line condition, it is necessary to make standards to maintain stability. One of them with WI or Work Instruction as a reference for production operators to carry out their work. With the condition of the production line that is already good, the only thing that needs to be done is to maintain the stability of the process. Work Instruction itself has been widely used by all industries to keep root employees working according to standards.